2021
DOI: 10.1007/s00344-021-10447-7
|View full text |Cite
|
Sign up to set email alerts
|

Plant Hormone Metabolome and Transcriptome Analysis of Dwarf and Wild-type Banana

Abstract: Gibberellin (GA), auxin (IAA) and brassinosteroid (BR) are indispensable in the process of plant growth and development. Currently, research on the regulatory mechanism of phytohormones in banana dwarfism is mainly focused on GA, and few studies are focused on IAA and BR. In this study, we measured the contents of endogenous GA, IAA and BR and compared the transcriptomes of wild-type Williams banana and its dwarf mutant across five successive growth periods. We investigated the relationship between hormones an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Another protein, glyceraldehyde-3-phosphate dehydrogenases (GAPDH) was also found in many plants' metabolic pathways of glycolysis that generates intermediate products for the primary metabolites such as amino acids (AAs) and fatty acids (FAs) (Schneider et al 2018;Zeng et al 2018;Wei et al 2022). The second largest protein involved in the biosynthesis of secondary metabolites pathways, three proteins were positively expressed out of 31 proteins, and similar results were found by (Zhang et al 2020;Deng et al 2022) in the same fungal affected Brazilian and Aifen No. 1 cultivars.…”
Section: Discussionsupporting
confidence: 80%
“…Another protein, glyceraldehyde-3-phosphate dehydrogenases (GAPDH) was also found in many plants' metabolic pathways of glycolysis that generates intermediate products for the primary metabolites such as amino acids (AAs) and fatty acids (FAs) (Schneider et al 2018;Zeng et al 2018;Wei et al 2022). The second largest protein involved in the biosynthesis of secondary metabolites pathways, three proteins were positively expressed out of 31 proteins, and similar results were found by (Zhang et al 2020;Deng et al 2022) in the same fungal affected Brazilian and Aifen No. 1 cultivars.…”
Section: Discussionsupporting
confidence: 80%
“…The IAA and ABA contents were significantly higher in tetraploid dwarf garlic. The significantly higher IAA was found in the dwarf bananas which likely regulated GA biosynthesis by negative feedback ( Deng et al, 2021 ). IAA was also found to induce the overexpression of OsIAA1 gene (member of Aux/IAA and auxin response factor), leading to shorter plant and loose architecture distinctively in rice ( Song et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, GA, BR, auxin and SLs control plant height through regulating cell elongation and cell [ 27 ]. GA and IAA have significant effects on banana dwarfing [ 28 ]. In other dwarf pine species, endogenous phytohormones are associated with dwarf formation.…”
Section: Discussionmentioning
confidence: 99%
“…GA2ox were only up-regulated in dwarf cultivar litchi samples, indicating GA might play an important role in regulating difference between vigorous and dwarf cultivars [ 46 ]. GA2ox for GA and tryptophan decarboxylase ( TDC ) and YUCCA for IAA were the most associated with plant height in banana [ 28 ]. In Chimonanthus praecox , transcriptome differential gene analysis showed that the elevated expression of the CpGA2ox and CpGAI gene in the signal transduction pathway might be the key mechanisms leading to dwarfing [ 47 ].…”
Section: Discussionmentioning
confidence: 99%